Evaluation and prediction of superhydrophobic surface durability using rolling wear tests and finite element analysis - Kyeongryeol Park; Hyunjong Kim; Kihwan Kim; Changwoo Lee; Amir Asadi; Ho Jun Kim; Kyungjun Lee (Materials & Design)
Superhydrophobic surfaces are defined by a contact angle exceeding 150°, achieved through microstructural surface treatment and hydrophobic chemical coatings. These surfaces exhibit self-cleaning properties as water droplets roll off. However, their hydrophobicity can degrade under external forces, presenting challenges in evaluating durability. In this study, aluminum, copper, and titanium were selected to investigate the durability of superhydrophobic surfaces. Micro-structured superhydrophilic surfaces were coated with hydrophobic Self-Assembled Monolayers to achieve superhydrophobicity. A rolling wear tester was self-developed to apply normal forces and assess durability by measuring changes in contact angle and self-cleaning performance after specified reciprocations of a rubber roller. Optical microscopy, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS) revealed that surface properties deteriorated due to the micro/nano-structure deformation and rubber debris deposits. Finite element analysis (FEA) was conducted to compare the robustness of copper nanopillars, aluminum cubic structures, and titanium hollow cubes, providing a predictive framework for durability assessment. The study demonstrates that durability predictions based on surface deformation and structural analysis can enhance our understanding of wear mechanisms and improve the practical application of superhydrophobic surfaces in various industries. This approach offers a promising methodology for evaluating the reliability of surface micro/nano-structures under mechanical stress.